Ichthyofaunal Biodiversity of Kharakuva Fish Market, Veraval, Gujarat, India - Joshi, Arti; Parmar, Ejaz A. Rahim; Temkar, G. S.; Desai, A. Y.; Bhatt, A. J. (International Journal of Bio-resource and Stress Management, 2018)
The coastline of Gujarat is 1,600 km long and salt marshes, sand-belts and gravel patches mark the topography. During the present study, total 94 finfish and 26 shellfish species belonging to 62 families and 18 orders were identified fromthe Kharakuva Fish market of Veraval Taluka from Gir-Somanth district of Gujarat, India. Data were collected with the help of local skilled fishermen and fish farmers from different locations of the different area forAugust, 2017 to March, 2018 on the ichthyofaunal diversity of Veraval coast, Gujarat. Identification of fishes was based on fresh or preserved specimens. They were identified by using standard taxonomic keys. The collected fish were identified up to species level. During the present study there were 94 finfish species under 14 order and 52 families, whereas 26 shellfish species belonging to 4 orders and 10 families were reported. Among the finfishes order Perciformes while in case of shellfishes order Decapoda represents abundance in landing. In case of family wise contribution Carangidae contributes a greater number of finfish species and family Penaeidae contributes a greater number of shellfish species. The price structure reported that shellfish fetches good value than that of finfish. Among finfish Protonibea diacanthus (Jew fish) and among the shellfish lobsters viz., Penulirus homarus and P. ornatus (Spiny lobster) fetches the highest price.